Mineral and chemical analyses of soils eaten by humans in Indonesia - Mahaney, William C.; Wink, Michael (International journal of environmental health research, 2010)
Five Javanese soil samples, including three earths eaten by humans as therapeutic medicine, were analyzed for their physical, mineral and chemical properties along with suitable control samples (not eaten). The eaten soils have a high content of hydrated halloysite and kaolinite, that is, clay minerals that are pseudoforms of the pharmaceutical Kaopectate. Along with hydrated halloysite in a ratio of nearly 1:1, the expandable clay mineral smectite is also present, but in much greater quantity than is usually found in Kaopectate. Among the chemical elements that may act as a stimulus for geophagy, only Na, Mn, K and S are possible candidates driving this behavior. Sodium is inherent in the minerals derived from the volcanic bedrock; and it is present in a form other than NaCl. Iron, which is often higher in soils eaten by both human and nonhuman primates, and has therefore been regarded in the past as a possible stimulus for geophagy, is relatively high in these soils, but does not have a higher concentration in the eaten soils relative to the uneaten soils in this group of samples. Cobalt and chromium, two important trace elements in human nutrition and diet, are marginally but not markedly higher in the eaten samples. The eaten soils in all cases have predominantly higher levels of 1:1 clay minerals than the 2:1 minerals which may predominate in some of the control soils, which some studies have associated with health problems. Soils can adsorb dietary toxins, present in the plant diet or those produced by microorganisms. Taking the toxic alkaloids quinine, atropine, sparteine, and lupanine as examples, it is evident that soils from Ampo (southern Java) have a very good adsorptive capacity, comparable to that of coal or charcoal. Other Javanese soils also adsorb these toxins, but to a lesser degree.